Outcome of Band Ligation in Esophageal Varices of Bangladeshi Children: A Tertiary Centre Experience (Bangladesh Journal of Child Health, 2017)
Background: Variceal bleeding is often a life threatening clinical situation in infants and children. Band ligation is the main endoscopic treatment for esophageal varices.Objective: To see the outcome of band ligation of esophageal varices in extra-hepatic and hepatic cases of portal hypertension.Methods: This prospective study was done in the Department of Pediatric Gastroenterology, Hepatology & Nutrition, Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh on 40 consecutive cases of esophageal varices enrolled from April, 2014 to March 2016. Every case was treated with band ligation followed by tab. propranolol. Cases were followed up for a minimum period of one year after the band ligation.Results: Age of the children was 2-12 years with mean age of 7.2±4.3 years and male:female ratio was 1.5:1. Out of 40 children, 32 (80%) were pre-hepatic and 8 (20%) hepatic (chronic liver disease with portal hypertension) causes. Only 1 session required in 50% pre-hepatic cases and multiple (2-3) sessions required in hepatic (100%) cases. Almost same number of band (average 2-3) required in every session of both cases. Grade-II esophageal varices with red sign were more common in prehepatic cases & severity of grading much more (grade-III & IV) in hepatic cases. Gastric varices were more common in hepatic (50%) cases than extra-hepatic (12.5%) cases. Recurrence of bleeding occurred in all hepatic (100%) cases and half (50%) of the pre-hepatic cases. Early re-bleeding was more common in hepatic (75%) cases & late re-bleeding in both pre-hepatic (43.7%) & hepatic (100%) cases. Minimal side effect like discomfort (10%) & Nausea (10%) were present after the procedure.Conclusion: Pre-hepatic was the most common etiology of portal hypertension in studied children. Fewer sessions were required in pre-hepatic cases than in hepatic cases. Severity of grading, re-bleeding & associated gastric varices were more common in hepatic cases. Band ligation was found to be the treatment of choice for the control of acute variceal bleeding and prevention of re-bleeding with less complications.Bangladesh J Child Health 2017; VOL 41 (1) :28-33